2019
DOI: 10.1152/ajpendo.00338.2019
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiota is a major regulator of androgen metabolism in intestinal contents

Abstract: Androgens exert important effects both in androgen-responsive tissues and in the intestinal tract. To determine the impact of the gut microbiota (GM) on intestinal androgen metabolism, we measured unconjugated (free) and glucuronidated androgen levels in intestinal contents from the small intestine, with a low bacterial density, and from cecum and colon, with a high bacterial density. Using a specific, sensitive gas chromatography-tandem mass spectrometry method, we detected high levels of glucuronidated testo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
125
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(130 citation statements)
references
References 51 publications
(59 reference statements)
4
125
0
1
Order By: Relevance
“…Some gut microbiota regulate androgen levels in the intestine by deglucuronidation to release free dihydrotestosterone from its glucuronide conjugates. 41 This also demonstrates the ability of gut microbiota to regulate androgen levels through different mechanisms. 41 Conversely, bacterial–host interactions can also be regulated by androgen levels.…”
Section: Effect Of Gut Microbiota On Blood Androgen Levelsmentioning
confidence: 90%
See 1 more Smart Citation
“…Some gut microbiota regulate androgen levels in the intestine by deglucuronidation to release free dihydrotestosterone from its glucuronide conjugates. 41 This also demonstrates the ability of gut microbiota to regulate androgen levels through different mechanisms. 41 Conversely, bacterial–host interactions can also be regulated by androgen levels.…”
Section: Effect Of Gut Microbiota On Blood Androgen Levelsmentioning
confidence: 90%
“… 41 This also demonstrates the ability of gut microbiota to regulate androgen levels through different mechanisms. 41 Conversely, bacterial–host interactions can also be regulated by androgen levels. 26 , 42 , 43 …”
Section: Effect Of Gut Microbiota On Blood Androgen Levelsmentioning
confidence: 90%
“…Interestingly, androgens also play a central role in sexual physiology, and disturbances in their action are associated with the development of different conditions in both men and women. Collden et al (2019) demonstrated that glucuronidases produced by the cecal microbiota can degrade the high content of testosterone and dihydrotestosterone found in the small intestine. The high content of free or unconjugated dihydrotestosterone found in the colon of healthy young mice of both sexes and men suggests that gut microbiota might be involved in the metabolism of intestinal androgens and can therefore affect the risk of androgen-related diseases in the distal intestine and probably also in remote anatomical sites.…”
Section: Hormone-gut Microbiome Axismentioning
confidence: 99%
“…In both mice and humans, androgens modulate the gut microbiota composition. 31,[63][64][65] Interestingly, mouse studies showed that the gut microbiota modulate androgen metabolism, 66 suggesting two-way crosstalk. Androgens also modulate microbial oscillations.…”
Section: Androgens Modulate Microbial Composition and Rhythmicitymentioning
confidence: 99%